2018
DOI: 10.3892/mmr.2018.9129
|View full text |Cite
|
Sign up to set email alerts
|

Synergistic apoptotic effects of silibinin in enhancing paclitaxel toxicity in human gastric cancer cell lines

Abstract: Gastric cancer (GC) is the 3rd leading cause of tumor‑associated mortality worldwide. The efficacy of paclitaxel, a frequently used GC chemotherapeutic agent, is hindered due to drug resistance, dose‑induced toxicity and adverse side effects. Silibinin, an active compound of a widely consumed dietary supplement, milk thistle extract, has recently been demonstrated to have strong antitumor efficacy in a human GC cell model. Thus, to enhance the efficacy of GC treatment, the present study evaluated whether silib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 34 publications
2
17
0
Order By: Relevance
“…Several publications have demonstrated that silibinin exhibits anti-tumor activity, e.g., in gastric cancer by enhancing paclitaxel toxicity [33] in glioblastoma by inducing apoptosis [34], and in ovarian cancer [35]. Here, we found that silibinin significantly restrains NSCLC cell proliferation, migration, invasion and EMT.…”
Section: Discussionmentioning
confidence: 50%
“…Several publications have demonstrated that silibinin exhibits anti-tumor activity, e.g., in gastric cancer by enhancing paclitaxel toxicity [33] in glioblastoma by inducing apoptosis [34], and in ovarian cancer [35]. Here, we found that silibinin significantly restrains NSCLC cell proliferation, migration, invasion and EMT.…”
Section: Discussionmentioning
confidence: 50%
“…This effect is incorporated with lower levels of cell division cycle 25C (cdc25C), cyclins (A, B1, D1, D3, and E), and Cdc2/ p34 as well as diminished activity of cyclin-dependent kinases (Errico et al, 2010). SIL is also proved to have the ability to induce program cell death through activation of caspases 3 and 9 along (Zhang et al, 2018). Moreover, SIL treatment decreased the growth and invasiveness of renal cancer 786-O cell while restraining the growth of cell and inducing program cell death in cancer Caki-1 cells through prevention of EGF, ERK1/2 (Raina et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Silibinin-induced apoptosis is associated with the modulation of apoptotic regulatory proteins in human pancreatic cancer cells [13][14][15]. The expression levels of cleaved caspase-3 and LC3B signi cantly increased in MIA PaCa-2 and PANC-1 cells following treatment with 200 µM silibinin (Figs.…”
Section: Silibinin Increases Autophagy and Apoptosis Signaling In Panmentioning
confidence: 92%
“…It can inhibit peroxidase and lipoxygenase [9,10]. Previous studies have shown that silibinin exerts anticancer effects on colon cancer, liver cancer, and breast cancer [11][12][13][14]. The role of silibinin in pancreatic cancer cells is as follows.…”
Section: Introductionmentioning
confidence: 99%